A novel design criterion for I-shape beams of steel MRF buildings in subduction-zone earthquake-prone areas. (February 2023) - Bosco, Melina; Tirca, Lucia
Abstract: This paper highlights the difference in the seismic response of 5-storey, 10-storey, and 15-storey steel moment resisting frame (MRF) buildings of various span lengths (6 m, 7.5 m, 9 m), located on Site class C in Vancouver, B.C., Canada, resulted under the mega-thrust subduction zone ground motions against crustal ground motions (GMs). To emphasize on the impact of GM duration on the seismic response of buildings, seven spectrally equivalent short and long duration record pair sets were selected from ground motion databases and employed in analyses. Numerical models that account for P -Δ effects and strength and stiffness degradation of steel MRF beams were used. Detailed nonlinear dynamic analyses were conducted to assess the collapse safety according to FEMA P695 (2009) methodology. The results indicated high probability of buildings' collapse under the long duration subduction GM suite, with a 38% average reduction in the median collapse capacity. Moreover, tall MRF buildings designed according to the current building code and steel design standard did not satisfy the collapse safety criteria when subjected to subduction GMs characterized by significant duration t 5-95  > 60 s, while the middle-rise buildings showed borderline pass. To overcome this drawback, a novel design criterion for I-shape MRF beams is proposed; hence, selecting MRF beam sections of Class 1 that are able to achieve aggregated fatigue coefficient greater than the proposed limit value, the occurrence of low cycle fatigue of plastic hinge region of MRF beams is delayed and the collapse safety criterium is achieved.